2012
DOI: 10.1186/1471-2407-12-378
|View full text |Cite
|
Sign up to set email alerts
|

miRNA-21 is developmentally regulated in mouse brain and is co-expressed with SOX2 in glioma

Abstract: BackgroundMicroRNAs (miRNAs) and their role during tumor development have been studied in great detail during the last decade, albeit their expression pattern and regulation during normal development are however not so well established. Previous studies have shown that miRNAs are differentially expressed in solid human tumors. Platelet-derived growth factor (PDGF) signaling is known to be involved in normal development of the brain as well as in malignant primary brain tumors, gliomas, but the complete mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 53 publications
1
27
0
Order By: Relevance
“…Following the irreversible depletion of miR-21, the expression of SOX2 was markedly reduced in mouse primary glioma cultures and human glioma cell lines. Therefore, miR-21 and SOX2 were concluded to be strongly regulated during embryogenesis, and define a distinct population of putative tumor cells (49). The results of the present study revealed higher miR-200b expression levels in the glioma tissues, as compared with the normal brain tissues.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…Following the irreversible depletion of miR-21, the expression of SOX2 was markedly reduced in mouse primary glioma cultures and human glioma cell lines. Therefore, miR-21 and SOX2 were concluded to be strongly regulated during embryogenesis, and define a distinct population of putative tumor cells (49). The results of the present study revealed higher miR-200b expression levels in the glioma tissues, as compared with the normal brain tissues.…”
Section: Discussionsupporting
confidence: 50%
“…In addition, SOX2 has been identified as a marker for undifferentiated and proliferating cells, with its expression upregulated in the most markedly anaplastic areas of glioblastomas and oligodendrogliomas (28). In mouse models (49), high expression of miR-21 has been observed during embryonic and newborn brain development, followed by a gradual reduction until undetectable at postnatal day 7, which correlates with SOX2 expression. miR-21 and SOX2 exhibited upregulation and an overlapping expression pattern in RCAS/tv-a generated mouse brain glioma specimens.…”
Section: Discussionmentioning
confidence: 99%
“…miR-21 regulates self-renewal of mouse spermatogonial stem cells [83]. A recent study identified increased miR-21 expression to regulate stem cells during embryonic brain development [84]. This expression of miR-21 correlates with Sox2 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Many previous studies demonstrated the direct interaction between miR-21 and SOX2. The induction of miR-21 strongly inhibited SOX2 expression andthe opposite effect was observed upon miR-21 inhibition strikingly (Polajeva et al, 2012;Singh et al, 2015;Trohatou et al, 2014;Yang and Rana, 2013). Previous studies in our lab found that heregulin-1β with SKP-SCs/ANA transplantation represented a powerful therapeutic approach, and facilitates the efficacy of acellular nerve allograft in peripheral nerve injury.…”
Section: Introductionmentioning
confidence: 77%
“…Silencing SOX2 expression in neural crest stem cells may reverse the inhibition of differentiation from neural crest stem cells to Schwann cells conducted by antagomir-21, which suggests that highly expressed miR-21 may promote this differentiation through inhibiting SOX2 protein expression (Ni et al, 2014). Other research shows that miR-21 might have specifically function by inhibiting the primarily level of SOX2 in human mesenchymal stem cells (MSCs) and might also act as a key molecule determining MSCs proliferation and differentiation (Trohatou et al, 2014;Yang and Rana, 2013).Also for other diseases such as glioma, miR-21 and SOX2 are revealed tightly regulated already during embryogenesis and define a distinct population with putative tumor cell of origin characteristics (Polajeva et al, 2012).…”
Section: Detection Of Mir-21 and Sox2 Expression In Hypoxic Schwann Cmentioning
confidence: 99%